The genome sequence of common reed, Phragmites australis (Cav.) Steud. (Poaceae) [version 1; peer review: 2 approved] - Maarten J. M. Christenhusz; Michael F. Fay (Wellcome Open Research, 2024)
We present a genome assembly from an individual Phragmites australis (the common reed; Streptophyta; Magnoliopsida; Poales; Poaceae). The genome sequence has a total length of 848.70 megabases. Most of the assembly is scaffolded into 24 chromosomal pseudomolecules, supporting the specimen being an allotetraploid (2n = 4x = 48). The three mitochondrial assemblies had lengths of 304.58, 92.24, and 76.54 kilobases and the plastid genome assembly had a length of 137.67 kilobases. Gene annotation of this assembly on Ensembl identified 47,513 protein-coding genes.